Sustained response with ixekizumab treatment of moderate-to-severe psoriasis with scalp involvement: results from three phase 3 trials (UNCOVER-1, UNCOVER-2, UNCOVER-3). (19th May 2017) - Reich, Kristian; Leonardi, Craig; Lebwohl, Mark; Kerdel, Francisco; Okubo, Yukari; Romiti, Ricardo; Goldblum, Orin; Dennehy, Ellen B.; Kerr, Lisa; Sofen, Howard
Abstract: Background: Scalp is a frequently affected and difficult-to-treat area in psoriasis patients. Objective: We assessed the efficacy of ixekizumab in the treatment of patients with scalp psoriasis over 60 weeks using the Psoriasis Scalp Severity Index (PSSI). Methods: In three Phase 3, multicenter, double-blind, placebo-controlled trials, patients with moderate-to-severe psoriasis in UNCOVER-1 ( N = 1296), UNCOVER-2 ( N = 1224) and UNCOVER-3 ( N = 1346) were randomized to subcutaneous 80 mg ixekizumab every two weeks (Q2W) or every four weeks (Q4W) after a 160 mg starting dose, or placebo through Week 12. Additional UNCOVER-2 and UNCOVER-3 cohorts were randomized to 50 mg bi-weekly etanercept through Week 12. Patients entering the open-label long-term extension (LTE) (UNCOVER-3) received ixekizumab Q4W; UNCOVER-1 and UNCOVER-2 included a blinded maintenance period in which static physician global assessment (sPGA) 0/1 responders were re-randomized to placebo, ixekizumab Q4W, or 80 mg ixekizumab every 12 weeks (Q12W) through Week 60. Results: In patients with moderate-to-severe psoriasis with baseline scalp involvement, PSSI 90 and 100 were achieved at Week 12 in higher percentages of patients treated with ixekizumab Q2W (81.7% and 74.6%) or ixekizumab Q4W (75.6% and 68.9%) compared with patients treated with placebo (7.6% and 6.7%; p < .001 each ixekizumab arm versus placebo) or etanercept (55.5% and 48.1%; p < .001 each ixekizumab arm versus etanercept). These outcomes were maintained through Week 60 of the maintenance (UNCOVER-1 and UNCOVER-2) and LTE (UNCOVER-3) period in patients who continued on ixekizumab Q4W. Conclusion: Ixekizumab was efficacious in treating scalp psoriasis in patients with moderate-to-severe psoriasis, with most patients achieving complete or near-complete resolution of scalp psoriasis and maintaining this response over 60 weeks.